Immobilisation of catalysts for applications in organic reactions - Noreldeen Hassan. Abdallah (2016)
The use of catalysts generally requires the immobilisation of the catalyst at specific locations, a requirement that can pose a significant challenge. The use of mesoporous silicate materials as supports offers some valuable advantages and can provide a more stable environment for catalysts. In this instance, this project was focused on the preparation, characterisation and optimization of immobilized catalysts (enzyme and metal based) for applications in organic reactions. The goal is to obtain an optimal catalytic performance combined with long-term operational stability. In order to achieve this goal, a detailed understanding of the solid supports, the catalysts, and of the immobilization process is essential. Cytochrome c and Candida antartica lipase B (CALB) were immobilised on to the mesoporous silicate SBA-15 and a porous spherical silicate material (PPS) in order to determine the influence of differences in the properties of supports such as pore volume, surface area and morphology on factors such as loading, activity and stability of enzymes. The catalytic activity of cytochrome c was similar on both supports, while the loading and catalytic activity of CALB on SBA-15 was higher when compared to PPS. These results indicate that the amount of adsorbed enzyme and activity are a reflection of the different surface areas, pore shapes and pore volumes of the two materials. Leaching of the enzyme from the support can result in substantial losses in activity, particularly on reuse. To overcome this disadvantage, it is necessary to utilise surface modification of the silica support to specifically bind the immobilised enzyme. In order to explore this effect, covalent attachment of Nickel/Cobalt-cyclam onto MCF were examined. The amount of cyclam modified onto the surface of MCF increased as the amounts of starting materials were increased. Ni/Co-cyclam modified materials were tested for their ability to immobilise His6-alanine racemase (HT-AlaR). The catalytic activity of immobilized HT-AlaR was comparable to ...